Thelytokous Diglyphus wani: A more promising biological control agent against agromyzid leafminers than its arrhenotokous counterpart - Su-jie DU; Fu-yu YE; Shi-yun XU; Wei-jie WAN; Jian-yang GUO; Nian-wan YANG; Wan-xue LIU (Journal of Integrative Agriculture)
Diglyphus wani (Hymenoptera: Eulophidae) is a dominant parasitoid that attacks agromyzid leafminers. Two reproductive types occur in D. wani: arrhenotoky (in which virgin females produce only male offspring; and virgin females mate with males to produce bisexual offspring) and thelytoky (in which virgin females produce female offspring). As a potential biological control agent, exploring the differences in the relevant biological parameters of both strains is necessary. In this study, comparisons between the two strains of D. wani were performed by evaluating the life table and host-killing rate. The thelytokous strain exhibited significantly better life table parameters than its arrhenotokous counterpart. Higher values for the intrinsic rate of increase, finite rate of increase, net reproductive rate, and fecundity were found in the thelytokous strain. The thelytokous strain also performed better than the arrhenotokous strain in terms of net parasitism, host-feeding, host-stinging, and total host-killing rates. Thus, populations of the thelytokous strain could grow fast and kill more hosts. In conclusion, the thelytokous strain of D. wani may be the more promising biological agent against agromyzid leafminers compared to its arrhenotokous counterpart. Also, since the thelytokous strain of D. wani is only known to produce females, it should be given priority in future biocontrol applications owing to the cost savings of breeding only females.